Measurement of the non-prompt D-meson fraction as a function of multiplicity in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; et al. (Journal of high energy physics, 2023)
The fractions of non-prompt (i.e. originating from beauty-hadron decays) D0 and D+ mesons with respect to the inclusive yield are measured as a function of the charged-particle multiplicity in proton-proton collisions at a centre-of-mass energy of $$ \sqrt{s} $$= 13 TeV with the ALICE detector at the LHC. The results are reported in intervals of transverse momentum (pT) and integrated in the range 1 < pT < 24 GeV/c. The fraction of non-prompt D0 and D+ mesons is found to increase slightly as a function of pT in all the measured multiplicity intervals, while no significant dependence on the charged-particle multiplicity is observed. In order to investigate the production and hadronisation mechanisms of charm and beauty quarks, the results are compared to PYTHIA 8 as well as EPOS 3 and EPOS 4 Monte Carlo simulations, and to calculations based on the colour glass condensate including three-pomeron fusion.